COMPARATIVE STUDY BETWEEN CAUDAL EPIDURAL STEROID INJECTION AND TRANSFORAMINAL BLOCK FOR POST-LUMBAR SURGERY SYNDROME - Dr. Chevuru Monica; Dr. Devaram Vijetha; Dr. Gundlakunta Swathi; Dr. Griddaluru Deepthi; Dr. K Krishna Chaitanya; Dr. Valluri Anil Kumar (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Introduction: Post-lumbar surgery syndrome (PLSS) may result, often attributed to epidural fibrosis. Minimally invasive interventions like caudal epidural steroid injections (CESI) offer relief, especially when surgical revisions have high risks. Transforaminal epidural steroid injections (TFESIs) are commonly used and target-specific, effectively managing PLSS unresponsive to conservative therapies. Materials and Methods: The study included 40 patients in each group (CESI and TFESI) who met specific criteria: aged 18-65, with a recent single-level nonfusion discectomy, evidence of epidural fibrosis (EF) on MRI, and persistent low back and leg pain unresponsive to conservative treatments. Exclusion criteria included multilevel EF, previous fusion surgery, recurrent disc hernia, and other spinal conditions. Numeric Rating Scale (NRS-11) and modified Oswestry Disability Index (mODI) were assessed before and after the procedure at various time points. Observations and Results: Age did not significantly differ between CESI (M = 52.78 ± 7.99) and TFESI (M = 49.65 ± 9.79) groups (p = 0.122). The gender distribution did not significantly differ between the CESI and TFESI groups (p = 0.823). The distribution of ASA categories did not significantly differ between CESI and TFESI groups (p = 0.822). BMI did not significantly differ between CESI and TFESI groups (p = 0.195). Among the NRS scores, only the 1st day showed a significant difference between the CESI and TFESI groups (p = 0.033). The mean NRS score for CESI at 1st day was 0.23 ± 0.39, while for TFESI it was 0.45 ± 0.51. Significant differences in Oswestry Disability Index scores were found at 6 hours (p = 0.001), 12 hours (p < 0.0001), 5th day (p = 0.002), and 1 week (p = 0.002) post-procedure, with CESI group reporting lower mean scores compared to TFESI at these time points. Discussion: CESI offered quicker pain alleviation and enhanced early functional progress than TFESI, especially during the initial week. Both methods demonstrated comparable long-term results in pain and disability scores by the 3-month follow-up. Conclusion: CESI provides better early symptom relief in PLSS, whereas CESI and TFESI are similarly effective over the long term. CESI might be favored for faster recovery, particularly in situations involving significant epidural fibrosis.